The Effect Of Profitability, Solvency And Liquidity Ratios On Stock Returns In Consumer Goods Sector Manufacturing Companies Listed On The Idx 2017-2022 - Kristin Natalia Sili Tokan; Pristin Prima Sari Sari; Johannes Maysan Damanik (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of profitability ratio (ROE), solvency ratio (DER) and liquidity ratio (CR) on stock retuns. Secondary data in the form of annual reports of manufacturing companies in the consumer goods industry sector in 2017-2022 is used as a sampling method. The results of the research conducted found that the profitability ratio variable has a negative effect on stock returns, the solvency ratio has a positive effect on stock returns, the liquidity ratio has a negative influence on stock returns and simultaneously the profitability ratio, solvency ratio, and liquidity ratio have an effect on stock returns.